The Fundamental Element of Social Contract In a Developmental State - Mbulaheni Mulaudzi (African Journal of Political Science)
The Conceptual Framework that underpins this article is that of advocating for a “Developmental state” that has the capacity to deliver services at national level but also creating a platform for the private sector to make a meaningful investment through trade and investment The article moves from the premise that  “Developmental state” should be one that is able to intervene in service delivery as well as to intervene in the running  of the economy especially as it relates to the role of the private sector in driving national and international goals. It is the argument of these article that for a “Developmental state” to become functional its should be comprised of meritocratic bureaucracy that is able to make use of the interventionist power in the same way that the East Asian Countries has done. As such the article arises from the argument that although the ANC led government has declared South Africa a “Developmental state”, such a state is still faced with numerous challenges that deter it to fulfill the requirements of a “Developmental state”. The study focus will also look at the extent at which the South African state is moving towards becoming a fully-fledged “Developmental state” regardless of the challenges been experienced and encountered.